Women Engineers–Past, Present and Future Scenario - Yadav, Savita (Journal of Engineering Education Transformations, 2016)
In modern times when we talk about the achievements and contributions in various fields made by men and women in the same breath, Is there really a need to discuss about the topic in concern "Women in Engineering". Indeed as they say "there is no smoke without fire", many research studies conducted by independent/funded organizations reveal startling facts regarding standing of women in male dominated arenas. Engineering is one such prominent field which has long been considered as a tough guys work. Owing to preconceived notions, lack of support, dismal encouragement and biasness, women often hesitate in taking up engineering as a career option. This paper summarizes the work done by pioneering studies existing in literature which have made significant say in the present condition of women in this field, the reasons which are holding back this bunch of talent, the hues and cries, and the possibility of further steps needed to mitigate this trend of downfall in the number of women engineers, thereby targeting engineering education in 2025 with no disparity between men and women.